'Real time'early warning indicators for costly asset price boom/bust cycles: a role for global liquidity - Lucia Alessi; Carsten Detken (European Central Bank (ECB), 2009)
We test the performance of a host of real and financial variables as early warning indicators for costly aggregate asset price boom/bust cycles, using data for 18 OECD countries between 1970 and 2007. A signalling approach is used to predict asset price booms that have relatively serious real economy consequences. We use a loss function to rank the tested indicators given policy makers' relative preferences with respect to missed crises and false alarms. The paper analyzes the suitability of various indicators as well as the relative performance of financial versus real, global versus domestic and money versus credit based liquidity indicators. We find that global measures of liquidity are among the best performing indicators and display forecasting records, which provide useful information for policy makers interested in timely reactions to growing financial imbalances, as long as aversion against type I and type II errors is not too unbalanced. Furthermore, we explore out-of-sample whether the most recent wave of asset price booms (2005-2007) would be predicted to be followed by a serious economic downturn.
Keywords: E37; E44; E51; 330; Early Warning Indicators; Leaning Against the Wind; Signalling Approach; Liquidität; Messung; Wirtschaftsindikator; Spekulationsblase; Frühwarnsystem; OECD-Staaten